Nonspecific toxicities of Streptococcus pyogenes and Staphylococcus aureus dCas9 in Chlamydia trachomatis - Wurihan, Wurihan (Pathog Dis, 2020)
Chlamydiae are common, important pathogens for humans and animals alike. Despite recent advancement in genetics, scientists are still searching for efficient tools to knock out or knock down the expression of chromosomal genes. We attempted to adopt a dCas9-based CRISPR interference (CRISPRi) technology to conditionally knock down gene expression in Chlamydia trachomatis using an anhydrotetracycline (ATC)-inducible expression system. Surprisingly, expression of the commonly used Streptococcus pyogenes dCas9 in C. trachomatis causes strong inhibition in the absence of any guide RNA (gRNA). Staphylococcus aureus dCas9 also shows strong toxicity in the presence of only an empty gRNA scaffold. Toxicity of the S. pyogenes dCas9 is readily observed with as little as 0.2 nM ATC. Growth inhibition by S. aureus dCas9 is evident starting at 1.0 nM ATC. In contrast, C. trachomatis growth was not affected by methionine-tRNA ligase overexpression induced with 10 nM ATC. We conclude that S. pyogenes and S. aureus dCas9 proteins in their current forms have limited utility for chlamydial research and suggest strategies to overcome this problem.